Tour Experience with Interactive Map Simulation based on Mobile Augmented Reality for Tourist Attractions in Banjarmasin City - Aulia Akhrian Syahidi; Joniriadi Joniriadi; Nanda Herven Waworuntu; Subandi Subandi; Kiyoshi Kiyokawa (The IJICS (International Journal of Informatics and Computer Science), 2022)
Tourist attractions are one of the attractions in the tourism sector, especially in the city of Banjarmasin. Along with the progress of the tourism sector, it is necessary to develop, provide facilities, management, and promotion. The purpose of this research is to build an application to identify tourist attractions in the City of Banjarmasin using Augmented Reality (AR) visualization by creating an interactive map simulation as a marker that will bring up three-dimensional objects, the application is called AR-AyoKeBanjarmasin. The method used in this research consists of Extreme Programming (XP) as a method in the software development process, Marker-Based Tracking as the main method in pattern detection techniques in marker images that will display three-dimensional objects that have been programmed in AR applications, A/B Testing method is used to select the interface design expected by potential users, Black- Box Testing as a method of testing application functionality, and User-Experience Questionnaire (UEQ) as a technique and instrument to evaluate User Experience (UX) when using the AR application. The results show that the design chosen for the user interface is design A so that it can be continued to the coding stage. Functional testing gives the result that all features in the application have functioned as expected and non-functionally involving 50 respondents using a UX approach stating that the application has implemented the user convenience aspect with an average value of 2.93 with the predicate of Excellent. So that the AR-AyoKeBanjarmasin application can be recommended for use by tourists